Sustainable tourism promotion through mobile gamification and reward systems for Chiang Mai Old Town, Thailand - Thinnukool, Orawit; Phrommas, Rattaphol; Kongdee, Nop; Jintapitak, Manissaward; Pitupumnak, Khanithep; Jarumaneerat, Tatiyaporn; Khuwuthyakorn, Pattaraporn (Frontiers in Computer Science, 2025)
The integration of digital technologies into tourism has opened innovative pathways to enhance visitor engagement, yet limited research explicitly examines the combined use of gamification and augmented reality (AR) in heritage contexts. This study explores the effectiveness of a “play to earn” approach through the Lanna Passport mobile application designed for Chiang Mai Old Town, Thailand. Utilizing AR, gamified challenges, and reward-based incentives, the app guides visitors through 25 key cultural sites, encouraging physical activity and immersive exploration. Evaluations demonstrate significantly increased engagement and satisfaction, particularly among younger demographics. Nonetheless, usability barriers for older users underscore the importance of designing intuitive interfaces. Results emphasize AR and gamification's potential to promote heritage appreciation and sustainability, offering insights for future application development targeted at diverse tourist groups.